Embeddedness in Lurik Business Sustainability in Klaten, Central Java, Indonesia - Riska Aryani Damayanti; Supriyadi Supriyadi; Ahmad Zuber (Profesional Muda Cendekia Publishing, 2021)
The existence of a lurik industrial center in Klaten, Central Java, Indonesia, has experienced ups and downs since 1950, where it is not uncommon for lurik producers to fall and most of them rise, and continue to pioneer the lurik business until now. This study aims to analyze in depth the sustainability of the lurik business in Klaten, Central Java, Indonesia, which is supported by the embeddedness in paseduluran ties. This research is studied through qualitative research methods with a phenomenological study approach, data collection using observation techniques, in-depth interviews, and documentation. The technique of selecting informants using purposive sampling. To ensure the validity of the data, the source triangulation technique was used, while the data analysis used the data analysis technique with the fixed comparison analysis method. The results of the study conclude that the sustainability of the lurik business in Klaten, Central Java, Indonesia, is embeddedness to paseduluran ties. In this research study, paseduluran is a tradition or culture that is binding in society based on the value of trust; tepo sliro; nrimo ing pandum; and reciprocity. Overall aspects are related to each other to form embeddedness.